Pengaruh Social Media Advertising Terhadap Purchase Intention Sportswear Merek Lokal Yang Dimediasi oleh Brand Trust Di Bandung Raya - Septiarini, Eka; Muthiah, Ceha; Sari, Charlina (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2024)
The social media revolution which was previously a networking platform for interacting and socializing is now one of the platforms for expanding business networks, markets and advertising media to reach potential consumers. The internet and growth of social media users open up opportunities to expand marketing networks to reach potential consumers. Social media advertising helps to advertise, product promotion, and sales offers. Social media advertising provides a visual stimulus that attracts potential consumers attention. This study aims to examine the effect of social media advertising on purchase intention of local sportswear brands in Bandung Raya mediated by brand trust with descriptive and associative quantitative methods. 183 have completed the questionnaire which were distributed through the Google form. Smart-PLS software was used as an analytical tool by testing the inner model and outer model. The research results showed that social media advertising has a significant positive effect on purchase intention of 41.5%, Social media advertising has a significant positive effect on brand trust of 66.0%, Brand trust has a significant positive effect on purchase intention of 29.7%, Brand trust has a significant positive effect mediating social media advertising on purchase intention of 19.6%.